Bond behaviour between H-shaped steel and concrete after freeze-thaw cycles - Yongjun Lin; Sihua Jiang; Shuiyun Zhong; Song Guo (Scientific Reports)
Abstract By conducting push-out tests, the bond behavior between H-shaped steel and concrete under different freeze-thaw (F–T) cycles (including failure modes, bond strength, and bond stress-slip curves) was investigated. The experiment considered one type of concrete (C35), three volumetric stirrup ratios (0.4%, 0.8%, and 1.2%), and three F–T levels (0, 25, and 50 cycles). Based on the experimental results, the effects of F–T cycles and stirrup ratio on the bond performance were systematically analyzed. The results showed that prior to F–T exposure, specimens with a stirrup ratio of 0.8% and an anchorage length of 380 mm / 560 mm exhibited splitting failure, while specimens with a stirrup ratio of 0.4% and an anchorage length of 380 mm experienced pull-out failure. As the number of F–T cycles increased, the failure mode shifted from splitting failure to push-out failure. After 50 F–T cycles, the bond strength of specimens with 380 mm and 560 mm anchorage lengths decreased to 82.2% and 84.7%, respectively, compared to the unexposed condition. Under the same F–T conditions, the pull-out force and bond strength of specimens with a 1.2% stirrup ratio were higher than those with 0.4%. The bond stress-slip curve shape remained generally consistent before and after F–T cycles, but the peak stress decreased and the slip at the peak load increased with more cycles. A regression model was also developed to describe bond strength degradation, providing a basis for predicting long-term performance. These findings clarify the deterioration pattern of steel–concrete bond under F–T conditions and offer a technical reference for the safety and durability assessment of composite structures in cold regions.